(untitled) (Indian Journal of Animal Production and Management, 2013)
The study on the managerial practices followed by the farmers rearing Jersey x Sahiwal cows revealed that 25.8 and 56.3 per cent of the farmers were feeding green fodder ad libitum and in limited quantity, respectively. Majority of the farmers i.e. 77.4 per cent were feeding dry fodder ad libitum. Only 5.3 per cent farmers were feeding optimum level of concentrate feed while majority of the farmers (81 per cent) were feeding restricted concentrate feed. Regular feeding of mineral mixture was practiced by 63.7 per cent of the farmers. All the farmers were aware of heat detection in cows and Artificial Insemination. Present study revealed that on an average, 2.43 inseminations were required for each conception. Most of thefarmers (91.68) provided kutcha housing to animals while 27.9 per cent farmers had manure disposal pits. Average hygiene levels were observed in most of the cases. All the dairy farmers allowed suckling by their calves before and after milking and followed full hand milking twice a day regularly. Weaning of calves was not followed. Mastitis was the major health problem faced by the farmers followed by theileriasis and FMD. Prevalent reproductive problems were repeat breeding, anoestrus and retained placenta. Most of the farmers (89%) were vaccinating the animals by the vaccines provided by Animal Husbandry Department and none of the farmers was following recommended vaccination and deworming schedule.